Early interpersonal neurobiological assessment of attachment and autistic spectrum disorders - Schore, Allan N. (Frontiers in Psychology, 2014)
There is now a strong if not urgent call in both the attachment and autism literatures for updated, research informed, clinically relevant interventions that can more effectively assess the mother infant dyad during early periods of brain plasticity. In this contribution I describe my work in regulation theory, an overarching interpersonal neurobiological model of the development, psychopathogenesis, and treatment of the early forming subjective self system. The theory models the psychoneurobiological mechanisms by which early rapid, spontaneous and thereby implicit emotionally-laden attachment communications indelibly impact the experience-dependent maturation of the right brain, the “emotional brain.” Reciprocal right-lateralized visual-facial, auditory-prosodic, and tactile-gestural nonverbal communications lie at the psychobiological core of the emotional attachment bond between the infant and primary caregiver. These affective communications can in turn be interactively regulated by the primary caregiver, thereby expanding the infant’s developing right brain regulatory systems. Regulated and dysregulated bodily-based communications can be assessed in order to determine the ongoing status of both the infant’s emotional and social development as well as the quality and efficiency of the infant-mother attachment relationship. I then apply the model to the assessment of early stages of autism. Developmental neurobiological research documents significant alterations of the early developing right brain in autistic infants and toddlers, as well profound attachment failures and intersubjective deficits in autistic infant-mother dyads. Throughout I offer implication of the theory for clinical assessment models. This work suggests that recent knowledge of the social and emotional functions of the early developing right brain may not only bridge the attachment and autism worlds, but facilitate more effective attachment and autism models of early intervention.